Shining Affiliates in the Age of Falsity: The Path to SME Economic Competitiveness – HR Intelligence and Marketer Competence - Firmansyah, Deri; Wahdiniwaty, Rahma; Laras, Titi; Suryana, Asep (International Journal of Business, Law, and Education, 2026)
The modern marketing era is increasingly challenged by the trend of affiliate marketing, a commission-based e-commerce strategy that uses independent marketers to increase sales through digital platforms. The affiliate marketing model, which has emerged as a path to economic competitiveness for SMEs in an era of falsity, is reviewed from the perspective of HR intelligence and marketer competency. The success of affiliate marketing programs and their contribution to GDP growth are also reviewed. To achieve this goal, a systematic literature review (SLR), partly adopting the PRISMA method, was conducted on several recent journals containing relevant content. The findings indicate that affiliate success in an era of falsity is inseparable from the perception, motivation, and intention to use e-commerce platforms, the HR intelligence and competency of independent marketers, the integration of AI and knowledge management, and the development of marketing strategies. Behind the rise of the affiliate marketing trend, it is often accompanied by the emergence of fake affiliates with various fraudulent operating methods. While there is no panacea to anticipate this, businesses, honest affiliates, and customers at least need layered controls and relatively preventative measures. Building a fair, transparent, and ethical relationship between advertisers and affiliates in an affiliate marketing engagement model is key to success, benefiting businesses, affiliates, customers, society, and economic growth. The synthesis of findings also confirms that a successful affiliate marketing model in an era of fake can strengthen the economic competitiveness of SMEs, contributing to GDP growth and the national economy. The brilliant affiliate model and its multiplier effect on the economic competitiveness of SMEs, affiliates, people’s purchasing power, and GDP are also presented.